My Journey to the Ants - deShazo, Richard D. (American Clinical and Climatological Association, 2009)
In this paper, I review the strange, unplanned and unexpected journey I have had with Solenopsis invicta, the imported fire ant. Through serendipity, good fortune and repeated invenomation, I have come to count as collaborators a number of entomologists, toxicologists, allergists and immunologists who have guided me on this journey to the ants. We now understand the mechanisms for the cutaneous reactions experienced by 50% of the exposed population stung per year, as well as the immunologic and toxicologic properties of the ants unique venom. Allergen immunotherapy to fire ant extracts has been demonstrated to protect patients from repeat anaphylaxis. Methods have been developed to prevent and treat massive sting attacks on frail elders, including those in residential and medical facilities. The potential beneficial effects of venom components are under investigation. And yes, the journey and the stings continue.